2004
DOI: 10.1523/jneurosci.0994-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Development and Behavior of the Dystrophic Growth Cone, the Hallmark of Regeneration Failure, in anIn VitroModel of the Glial Scar and after Spinal Cord Injury

Abstract: We have developed a novel in vitro model of the glial scar that mimics the gradient of proteoglycan found in vivo after spinal cord injury. In this model, regenerated axons from adult sensory neurons that extended deeply into the gradient developed bulbous, vacuolated endings that looked remarkably similar to dystrophic endings formed in vivo. We demonstrate that despite their highly abnormal appearance and stalled forward progress, dystrophic endings are extremely dynamic both in vitro and in vivo after spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
250
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(263 citation statements)
references
References 50 publications
10
250
2
1
Order By: Relevance
“…This indicates that siRNA transfection decreased the inhibitory activity of the CSPGs present in the CM. Although one study has shown that the concentration of CSPG at a spot border is consistently higher if the spot is allowed to dry (Tom et al, 2004), we found that the concentration of CSPG on the spot is uniform if the spot is incubated in a humidified chamber (Fig. 5C).…”
Section: Chpf Sirna Reduces Gag Chain Production By Astrocytescontrasting
confidence: 54%
“…This indicates that siRNA transfection decreased the inhibitory activity of the CSPGs present in the CM. Although one study has shown that the concentration of CSPG at a spot border is consistently higher if the spot is allowed to dry (Tom et al, 2004), we found that the concentration of CSPG on the spot is uniform if the spot is incubated in a humidified chamber (Fig. 5C).…”
Section: Chpf Sirna Reduces Gag Chain Production By Astrocytescontrasting
confidence: 54%
“…In addition, our confocal results indicate preservation of CSPGs after decellularization. CSPGs are known to be potent neurite inhibitors [11,12,60,64]. By maintaining CSPG presence in the matrix, this has the potential to prevent nerve growth into the nucleus pulposus.…”
Section: Discussionmentioning
confidence: 99%
“…These sprouting tips of severed axons then remain stalled in place without further functional growth. Interestingly, these dystrophic growth cones are actually dynamic structures with continuing turnover of membrane components and are extremely dynamic in vitro and in vivo (Kerschensteiner et al, 2005;Tom et al, 2004b). Time-lapse video of these dystrophic endings illustrates repeated episodes of endocytosis and efforts to send out membrane veils (Tom, et al, 2004b).…”
Section: Nonpermissive Environment For Regeneration In the Cns Growthmentioning
confidence: 99%
“…Interestingly, these dystrophic growth cones are actually dynamic structures with continuing turnover of membrane components and are extremely dynamic in vitro and in vivo (Kerschensteiner et al, 2005;Tom et al, 2004b). Time-lapse video of these dystrophic endings illustrates repeated episodes of endocytosis and efforts to send out membrane veils (Tom, et al, 2004b). The failure of these dystrophic growth cones to continue growing to produce long-distance regeneration appears to be related to the inhibitory and nonpermissive nature of the injured brain and spinal cord.…”
Section: Nonpermissive Environment For Regeneration In the Cns Growthmentioning
confidence: 99%
See 1 more Smart Citation